ACCESSIBILITY TO WOMEN'S HEALTHCARE SERVICE DURING PREGNANCY AND POSTPARTUM - Sheila Milena Pessoa dos Santos; Lais Vasconcelos Santos; Jéssica Oliveira Rodrigues; Lara Caline Santos Lira; Laianne Barbosa de Souza; Ueigla Batista da Silva (Universidade Federal do Paraná, 2016)
The objective of this study was to analyze accessibility to women's healthcare service during pregnancy and postpartum. A documental, exploratory and descriptive study, with a quantitative approach, was conducted with a sample of 69 women who were pregnant or in postpartum, from January 2012 to April 2014. A semi-structured questionnaire was used for data collection, and descriptive statistics and specific literature were used for data analysis. We identified poor medical records; women with no prenatal consultations; a low number of women who were submitted to breast inspection procedures, gynecological examination and dentist appointments; and a low number of accomplished tests recommended by the Rede Cegonha program, linked to the municipality. This research is expected to serve as support to understand how current medical actions work and to acknowledge the existence of accessibility barriers to woman's healthcare service and the possibility of creating new strategies to improve medical care during pregnancy and postpartum.